Ectoparasites Diversity on Rodents and Shrews at Scrub Typhus Endemic Vellore District of Tamil Nadu, India - Philip Samuel Paulraj; Govindarajan Renu; Krishnamoorthi Ranganathan; Rajamannar Veeramanoharan; Ashwani Kumar (Tehran University of Medical Sciences, 2022)
Background: Rodents and shrew living in the vicinity of human beings perform significant role to harbor different species of ectoparasites and thus act as the reservoir host for the spread of diseases to human and animals. Methods: This study was undertaken to determine the species composition of the medically important ectoparasites present in the scrub typhus affected places of Vellore District using wonder and Sherman traps for trapping of live Rodent/Shrew during September 2017 to August 2018. Results: Rodent/shrew hosts belonged to two Families, three sub families and five genera and five different species. These animals carried 23 species of ectoparasites including 17 trombiculid mites, two non-trombiculid mites, two ticks and two fleas. A total of 940 chigger mites were collected which belonged to three Tribes, six Genera, two Subgenera and 17 species. Adult mites collected belonged to two families, three genera and three species. Ticks collected were classified under one family, two genera and two species. Fleas fall under one family, one subfamily, one tribe, one genus and two species. Conclusion: This is the first record of 14 species of chigger mites and three species of adult mites from Vellore District, Tamil Nadu. Surveillance of these keystone ectoparasites helped to identify the medically important disease vectors causing acari-borne zoonotic diseases.